Competence of preoperative methods of staging in rectal cancer treated by short-term regimen of high-dose fractionated preoperative radiotherapy - Grzela, Monika; Windorbska, Wiesława (Contemporary Oncology/Współczesna Onkologia, 2002)
The Swedish Rectal Cancer Trial demonstrated that a short-term regimen of high-dose fractionated preoperative radiotherapy (5x5 Gy) reduced the local recurrence rates and improved overall survival. This has an impact on the primary treatment of rectal cancer. Postoperative radiotherapy is indicated in patients in Astler-Coller stage B2 and C (pT3,T4N+). By recommending a preoperative approach, it is important to exclude patients with low risk of having a local recurrence, mainly those with a T1 or T2N0 lesion as well as those with metastatic disease. To avoid irradiation of such tumors accurate preoperative imaging should be used. The purpose of this study was to analyse how many patients treated by preoperative short-term regimen of radiotherapy in the Regional Center of Oncology in Bydgoszcz were in Astler-Coller stage A or B1 and whether it is possible to recognize them by using accurate preoperative imaging. In the period between February 1999 and April 2002, 31 patients with rectal cancer were treated by preoperative short-term regimen of radiotherapy in the Regional Center of Oncology in Bydgoszcz. The disease stage was set basing on transrectal ultrasonography in 5 patients (16.1%), computerized tomography of pelvis in 15 patients (48.4%) and on both of them in 11 patients (35.5%). Chest X Ray and abdominal ultrasonography were performed in all patients. Conclusions: 1. Over one-fifth of subjects treated with a short-term regimen of high-dose fractionated preoperative radiotherapy would not require any adjuvant radiotherapy in postoperative course. 2. A routine preoperative diagnostic procedure alone is not sufficient to select which subjects would not require radiotherapy in postoperative treatment. 3. There is a good correlation between pre- and postoperative evaluation of tumor (T) and rather poor correlation in such an evaluation of nodes involvement (N), according to TNM classification.